Gingival health status among a sample of Malaysian patients attending the periodontics clinic International Islamic University Malaysia - Farid, Farhana; Fo'ad, Farhanah; Hilal Abbood Al-Bayati, Lina; Kamil, Wisam Alaa (2011)
Gingivitis is an inflammation of the gingiva with no detachment of junctional epithelium from its original level at the tooth surface.1,2 The accumulation of plaque will induce gingivitis and removing of it will reverse the condition.3 The severity and duration of the response depend on local factors, systemic factors, medication and malnutrition effects to plaque-host interaction.4 The oral hygiene status of the individuals determined the prev-alence of gingivitis which explains the higher prevalence and ex-tents among males and adolescent who commonly have poor oral hygiene.5